Positive electrode active material and preparation method thereof, solid-state battery and electrical equipment

By forming a coating layer containing niobium oxide and solid electrolyte on the surface of the high-nickel cathode material, the thermal stability and interface reaction problems of the high-nickel cathode material are solved, and the safety performance and electrochemical performance of the battery are improved.

CN118263422BActive Publication Date: 2025-01-21BEIJING EASPRING MATERIAL TECH CO LTD

Patent Information

Application Number
CN202410382949.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2025-01-21
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

The thermal stability of high-nickel ternary cathode materials is low, resulting in a decrease in safety performance. There are serious spatial charge layer and interface side reactions in the interface between the solid-state battery and the solid-state electrolyte, affecting the capacity and rate performance of the battery.

Method used

A niobium-doped high-nickel material is used as a substrate, and a first coating layer including a niobium-containing oxide is formed on its surface, and a second coating layer including a solid electrolyte is formed on the surface of the first coating layer as a buffer layer. Improve the conduction of lithium ions and reduce interface side reactions.

Benefits of technology

It improves the safety performance, rate performance and capacity of the battery, and enhances the conduction and interface stability of lithium ions by reducing the space charge layer and interface side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118263422B_ABST
    Figure CN118263422B_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode active material and a preparation method thereof, a positive electrode plate, a solid-state battery and an electric device. The positive electrode active material comprises a substrate, a first coating layer and a second coating layer. The substrate comprises Li 1+b (Ni 1‑x1‑x2 Co x1 Mn x2 ) 1‑y‑z Nb y M z O2, ‑0.5≤b≤0.3, 0.05≤x1≤0.3, 0.05≤x2≤0.3, 0<y≤0.01, 0≤z≤0.01, M includes at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B and Al; a first coating layer is formed on at least a portion of the surface of the substrate, the first coating layer includes niobium oxide, and the niobium oxide includes Li u Nb 1‑V M′ V O3, wherein 0.5≤u≤1.2, 0≤v<1, M′ comprises at least one of Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Ti, Zr, Hf, Mn, W, Mo, B, Al, Ga, In, Ge and Sn; the second coating layer is formed on at least a portion of the surface of the first coating layer, and the second coating layer comprises a solid electrolyte. The positive electrode active material can improve the safety performance, rate performance and capacity of the battery containing the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a positive electrode active material and a preparation method thereof, a solid-state battery and an electrical device. Background Art

[0002] As consumers' requirements for the energy density and driving range of power batteries increase year by year, the safety performance of lithium-ion batteries has received more and more attention. The liquid organic electrolyte used in traditional lithium-ion batteries is prone to thermal runaway under certain working conditions, causing safety hazards such as combustion and explosion of batteries and vehicles. In contrast, non-flammable solid electrolytes can significantly improve safety, and the negative electrode can use lithium metal with higher energy density to increase the battery energy density. Therefore, the development of solid-state lithium batteries using solid electrolytes has become a recognized development direction in the lithium battery industry.

[0003] In solid-state lithium batteries, positive and negative electrodes and solid electrolytes are the most critical materials that affect battery performance. Among positive electrode materials, lithium nickel cobalt manganese ternary positive electrode materials have the advantage of high gram capacity, which has led to their rapid development and has become a competitive material system in the field of high-mileage passenger cars. Ternary materials are mainly divided into LiNi according to different nickel-cobalt-manganese composition ratios. 1 / 3Co 1 / 3 Mn 1 / 3 O2(NCM111),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523),LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.10 Al 0.05O2 (NCA), etc. With the increase of nickel content, the gram capacity and energy density of ternary positive electrode materials will be significantly improved. In particular, for high-nickel ternary materials with a Ni content of more than 90 mol%, the gram capacity can reach more than 210 mAh / g, and the energy density of the matching battery can reach 320 Wh / kg. Although high-nickel multi-element positive electrode materials can significantly improve the specific capacity and energy density of the material, the thermal stability is significantly reduced. The temperature at which the thermal runaway of the material occurs is lower, which will significantly reduce the safety performance of the material. This is the main reason that currently limits the large-scale application of high-nickel ternary materials, and it is also the root cause of the current "safety anxiety" of new energy vehicles. In addition, there are serious space charge layers and interface side reactions between the layered positive electrode material and the solid electrolyte. The space charge layer at the interface will affect the transmission of lithium ions, causing the attenuation of the capacity and rate performance of the solid-state battery. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one object of the present invention is to provide a positive electrode active material and a preparation method thereof, a solid-state battery and an electrical device, wherein the positive electrode active material can improve the safety performance, rate performance and capacity of the battery containing the positive electrode active material.

[0005] In one aspect of the present invention, the present invention provides a positive electrode active material. According to an embodiment of the present invention, the positive electrode active material comprises:

[0006] A matrix comprising Li 1+b (Ni 1-x1-x2 Co x1 Mn x2 ) 1-y-z Nb y M z O2, -0.5≤b≤0.3, 0.05≤x1≤0.3, 0.05≤x2≤0.3, 0<y≤0.01, 0≤z≤0.01, M includes at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B and Al;

[0007] The first coating layer is formed on at least a portion of the surface of the substrate, and the first coating layer includes niobium oxide, the niobium oxide includes Li u Nb 1-v M′ v O3, wherein 0.5≤u≤1.2, 0≤v<1, and M′ comprises at least one of Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Ti, Zr, Hf, Mn, W, Mo, B, Al, Ga, In, Ge and Sn;

[0008] A second coating layer is formed on at least a portion of a surface of the first coating layer, and the second coating layer includes a solid electrolyte.

[0009] According to the positive electrode active material of the embodiment of the present invention, it uses a niobium-doped high-nickel material as a matrix, which can effectively improve the cycle performance of the high-nickel material, and forms a first coating layer including niobium oxide on at least part of the surface of the matrix, and then forms a second coating layer including a solid electrolyte on at least part of the surface of the first coating layer, that is, the first coating layer is used as a buffer layer between the matrix and the second coating layer. On the one hand, Nb in the matrix can be chemically bonded with Nb in the niobium oxide in the first coating layer to improve the conduction of lithium ions. On the other hand, after the second coating layer including the solid electrolyte is matched with the matrix, if there is a chemical potential gradient between the two, the electrochemical window does not match, and it is easy to decompose and precipitate redox reactions of electrons and ions, which are called redox decomposition reactions of the solid electrolyte itself, and generate a space charge layer. At the same time, due to the difference in the stability of the anions of the matrix material and the solid electrolyte material, during the charge and discharge cycle, the anions of the two will diffuse to a certain extent, and the anions will be replaced at the interface. The above interface failure behaviors will lead to the occurrence of interface side reactions and increase the interface impedance. The first coating layer including niobium oxide is used as a buffer layer. On the one hand, since the chemical potential of the first coating layer including niobium oxide of the present invention is between the substrate and the solid electrolyte, it can buffer the problem of large chemical potential between the substrate and the second coating layer. On the other hand, it can inhibit the formation of lithium depletion layer at the interface between the substrate 11 and the second coating layer 13, effectively reduce the large interface resistance caused by the space charge layer, so as to protect the solid electrolyte from the high chemical potential of the positive electrode active material, and also play a role in inhibiting the interface side reaction. That is, the first coating layer including niobium oxide can reduce the space charge layer and interface side reaction between the substrate and the second coating layer, further improve lithium ion transmission, and improve the capacity and rate performance of the battery. On the other hand, after the first coating layer is introduced, the interface polarization between the substrate and the second coating layer becomes smaller, thereby improving the safety performance of the positive electrode active material. In addition, the second coating layer containing the solid electrolyte can improve the interface contact between the positive electrode active material and the solid electrolyte, reduce the interface impedance, and provide interface stability guarantee for the electrochemical cycle of the solid-state battery. Therefore, the positive electrode active material of the present invention can improve the safety performance, rate performance and capacity of the battery containing it.

[0010] In addition, the positive electrode active material according to the above embodiment of the present invention may also have the following additional technical features:

[0011] In some embodiments of the present invention, the niobium-containing oxide satisfies at least one of the following conditions:

[0012] The 2θ angle corresponding to the (012) peak position in the XRD pattern is not less than 23.7°;

[0013] The 2θ angle corresponding to the (104) peak position in the XRD pattern is not less than 32.7°;

[0014] The 2θ angle corresponding to the (110) peak position in the XRD pattern is not less than 34.8°;

[0015] The unit cell volume is less than or equal to

[0016] The unit cell parameters a and c satisfy c / a = 2.690 ± 0.005;

[0017] The crystal structure density is 4.630 ± 0.005 g / cm 3 ;

[0018] The ionic conductivity of the niobium-containing oxide is 1.0×10 -6 S / cm - 1.0×10 -4 S / cm, preferably 1.0×10 -5 S / cm - 1.0×10 -4 S / cm.

[0019] Thus, the rate performance and capacity of the battery can be improved.

[0020] In some embodiments of the present invention, the oxidation potential of the solid electrolyte is not higher than 4V. Thus, the interfacial contact between the positive electrode active material and the solid electrolyte can be improved, the interfacial impedance can be reduced, and the interfacial stability guarantee for the electrochemical cycle of the solid-state battery can be provided.

[0021] In some embodiments of the present invention, the solid electrolyte includes at least one of sulfide solid electrolytes, inverse perovskite compound solid electrolytes, and borohydride solid electrolytes. Thus, the interfacial impedance between the positive electrode active material and the solid electrolyte can be reduced, and the electrochemical performance of the battery can be improved.

[0022] In some embodiments of the present invention, the sulfide solid electrolyte includes Li6PS5Cl, Li 4-d Ge 1-d P d S4, Li 10 GeP2S 12 、Li 10 SnP2S 12 、Li2S-P2S5、Li2S-SiS2、Li2S-B2S3、LiSiPSCl、LiSiPSBr, and LiSiPSI, where 0 < d < 1. Thus, the interfacial impedance between the positive electrode active material and the solid electrolyte can be reduced, and the electrochemical performance of the battery can be improved.

[0023] In some embodiments of the present invention, the antiperovskite compound solid electrolyte includes Li 3-em M e m O 1- n A n Hal, wherein Hal includes at least one of F, Cl, Br and I, 1≤e≤4, 0 <m<1,0<n<1,M e Including Na + , K + , Rb + , Cs + Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , B 3+ 、Al 3+ , Ga 3+ 、In 3+ Sc 3+ , Y 3+ ,La 3+ 、Si 4+ ,Ge 4+ 、Ti 4+ 、Zr 4+ and Hf 4+ At least one of the following: A includes a divalent anion. Thus, the interface impedance between the positive electrode active material and the solid electrolyte can be reduced, and the electrochemical performance of the battery can be improved.

[0024] In some embodiments of the present invention, A includes S 2- 、Se 2- and Te 2- At least one of .

[0025] In some embodiments of the present invention, the borohydride solid electrolyte includes Li r TH s , wherein 0<r, 0<s, and T includes at least one of B, C, N and Al. Thus, the interface impedance between the positive electrode active material and the solid electrolyte can be reduced, and the electrochemical performance of the battery can be improved.

[0026] In some embodiments of the present invention, based on the total mass of the substrate, the content of Nb in the substrate is A, based on the total mass of the first coating layer, the content of Nb in the first coating layer is B, and A < B. In this way, the transmission of lithium ions between the substrate and the second coating layer can be improved, and the capacity and rate performance of the battery can be improved.

[0027] In some embodiments of the present invention, A is 0.001 wt%-0.6 wt%, preferably 0.01 wt%-0.4 wt%.

[0028] In some embodiments of the present invention, B is 60.0 wt%-75.0 wt%, preferably 62.0 wt%-70.0 wt%.

[0029] In some embodiments of the present invention, along the direction from the substrate to the second coating layer, the volume average particle size Dv50 of the substrate is C, the volume average particle size Dv50 of the niobium oxide is D, and the volume average particle size Dv50 of the solid electrolyte is E, and C≥D≥E. Thus, sufficient interface contact between the substrate and the first coating layer and sufficient interface contact between the first coating layer and the second coating layer can be achieved, the interface impedance can be reduced, the transmission of lithium ions can be improved, and the rate performance and capacity of the battery can be improved.

[0030] In some embodiments of the present invention, C is 3 μm-20 μm, preferably 3 μm-10 μm, and more preferably 3 μm-6 μm.

[0031] In some embodiments of the present invention, D is 0.1 μm-3 μm, preferably 0.1 μm-1 μm, and more preferably 0.1 μm-0.5 μm.

[0032] In some embodiments of the present invention, E is 0.01 μm-0.1 μm, preferably 0.01 μm-0.08 μm, and more preferably 0.01 μm-0.05 μm.

[0033] In some embodiments of the present invention, the mass ratio of the substrate to the first coating layer and the second coating layer is (98.10-99.19): (0.80-1.60): (0.01-0.30). Thus, the safety performance, rate performance and capacity of the battery containing the substrate can be improved.

[0034] In a second aspect of the present invention, the present invention provides a method for preparing a positive electrode active material, comprising:

[0035] A first coating layer is formed on at least a portion of the surface of a substrate, wherein the substrate includes Li 1+b (Ni 1-x1- x2 Co x1 Mn x2 ) 1-y-z Nb y M zO2, -0.5≤b≤0.3, 0.05≤x1≤0.3, 0.05≤x2≤0.3, 0<y≤0.01, 0≤z≤0.01, M includes at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B and Al, the first coating layer includes niobium oxide, the niobium oxide includes Li u Nb 1-v M′ v O3, wherein 0.5≤u≤1.2, 0≤v<1, and M′ comprises at least one of Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Ti, Zr, Hf, Mn, W, Mo, B, Al, Ga, In, Ge and Sn;

[0036] A second coating layer is formed on at least a portion of the surface of the first coating layer, the second coating layer including a solid electrolyte.

[0037] Therefore, the above-mentioned positive electrode active material can be prepared by adopting this method, thereby improving the safety performance, rate performance and capacity of the battery containing the positive electrode active material.

[0038] In some embodiments of the present invention, the first coating layer is formed on at least a portion of the surface of the substrate by the following steps: mixing and sintering the substrate and the niobium-containing oxide at 300° C.-500° C., and keeping the mixture at this temperature for 0.5 h-12 h.

[0039] In some embodiments of the present invention, the second coating layer is formed on at least a portion of the surface of the first coating layer by the following steps: mixing and sintering the substrate forming the first coating layer with the solid electrolyte at 60°C-400°C and keeping the mixture warm for 0.5h-5h.

[0040] In the third aspect of the present invention, the present invention provides a positive electrode sheet, comprising the positive electrode active material described in the first aspect of the present invention or the positive electrode active material obtained by the method described in the second aspect of the present invention. Thus, the safety performance, rate performance and capacity of the battery containing the positive electrode sheet can be improved.

[0041] In a fourth aspect of the present invention, the present invention provides a solid-state battery, comprising the positive electrode sheet described in the third aspect of the present invention. Thus, the battery has excellent safety performance, rate performance and capacity.

[0042] In the fifth aspect of the present invention, the present invention proposes an electrical device, including the solid-state battery described in the fourth aspect of the present invention.

[0043] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0045] Figure 1 Schematic diagram of the structure of a positive electrode active material according to an embodiment of the present invention.

[0046] Figure 2 1 is a schematic flow chart of a method for preparing a positive electrode active material according to an embodiment of the present invention.

[0047] Figure 3 This is a SEM image of the positive electrode material matrix prepared in Example 1.

[0048] Figure 4 is a SEM image of the positive electrode active material prepared in Example 1.

[0049] Figure 5 It is the XRD spectrum of the nickel-cobalt-manganese multi-element material coated with lithium niobium oxide prepared in Example 1 and the positive electrode material matrix in Comparative Example 1.

[0050] Figure 6 This is a SEM image of the positive electrode material matrix prepared in Comparative Example 3.

[0051] Figure 7 It is the cycle curve of the solid-state battery of Example 1 and Comparative Examples 1 to 5. DETAILED DESCRIPTION

[0052] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0053] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0054] In one aspect of the present invention, the present invention provides a positive electrode active material. According to an embodiment of the present invention, reference Figure 1 The positive electrode active material 10 includes: a substrate 11 , a first coating layer 12 and a second coating layer 13 .

[0055] According to an embodiment of the present invention, the matrix 11 includes Li 1+b (Ni 1-x1-x2 Co x1 Mn x2 ) 1-y-z Nb y M z O2, -0.5≤b≤0.3, 0.05≤x1≤0.3, 0.05≤x2≤0.3, 0<y≤0.01, 0≤z≤0.01, M includes at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B and Al.

[0056] According to some embodiments of the present invention, the Li 1+b (Ni 1-x1-x2 Co x1 Mn x2 ) 1-y-z Nb y M z b in O2 satisfies -0.5≤b≤0.3, for example, b is -0.5, -0.4, -0.3, -0.2, -0.1, 0.1, 0.2, 0.3, etc. Thus, the matrix 11 includes lithium ions of this content, which can increase the specific capacity of the positive electrode active material, so that the battery has a higher capacity.

[0057] According to some embodiments of the present invention, the Li 1+b (Ni 1-x1-x2 Co x1 Mn x2 ) 1-y-z Nb y M z In O2, x1, x2, y and z satisfy 0.05≤x1≤0.3, 0.05≤x2≤0.3, 0<y≤0.01, 0≤z≤0.01, for example, x1 is 0.05, 0.15, 0.2, 0.25, 0.3, etc.; x2 is 0.05, 0.15, 0.2, 0.25, 0.3, etc.; y is 0.001, 0.003, 0.005, 0.007, 0.01, etc.; z is 0, 0.003, 0.005, 0.007, 0.01, etc. Therefore, by using a high nickel material doped with niobium of this content as the substrate 11, the cycle performance of the substrate 11 can be effectively improved.

[0058] According to an embodiment of the present invention, the first coating layer 12 is formed on at least a portion of the surface of the substrate 11, and the first coating layer 12 includes niobium oxide, and the niobium oxide includes Li u Nb 1-v M′ vO3, wherein 0.5≤u≤1.2, 0≤v<1, and M′ comprises at least one of Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Ti, Zr, Hf, Mn, W, Mo, B, Al, Ga, In, Ge and Sn. Thus, on the one hand, Nb in the niobium oxide in the first coating layer 12 can be chemically bonded with Nb in the substrate 11 to improve the conduction of lithium ions. On the other hand, since the chemical potential of the first coating layer 12 containing niobium oxide in the present invention is between the substrate 11 and the solid electrolyte, the large gradient effect of the chemical potential between the substrate 11 and the second coating layer 13 can be buffered. On the other hand, the first coating layer 12 containing niobium oxide is used as a buffer layer to inhibit the formation of a lithium depletion layer at the interface between the substrate 11 and the second coating layer 13, and the large interface resistance caused by the space charge layer can be effectively reduced to protect the second coating layer 13 containing the solid electrolyte from the high chemical potential of the substrate 11, and also play a role in inhibiting interface side reactions. That is, the first coating layer 12 containing niobium oxide can reduce the space charge layer and interface side reactions between the substrate 11 and the second coating layer 13, further improve lithium ion transmission, and improve the capacity and rate performance of the battery. On the other hand, after the first coating layer 11 is introduced, the interface polarization between the substrate 12 and the second coating layer 13 becomes smaller, thereby improving the safety performance of the positive electrode active material 10.

[0059] According to some embodiments of the present invention, the Li u Nb 1-v M′ v In O3, u and v satisfy 0.5≤u≤1.2, 0≤v<1, for example, u is 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, etc.; v is 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc.

[0060] According to some embodiments of the present invention, the 2θ angle corresponding to the (012) peak in the XRD spectrum of the niobium-containing oxide is not less than 23.7°, the 2θ angle corresponding to the (104) peak is not less than 32.7°; the 2θ angle corresponding to the (110) peak is not less than 34.8°; the unit cell volume is less than or equal to The unit cell parameters a and c satisfy c / a=2.690±0.005; the crystal structure density is 4.630±0.005g / cm 3 .

[0061] In the present invention, the above-mentioned niobium oxide-containing phase test, unit cell volume test, unit cell parameter a and c test, and crystal structure density test method include: using X-ray diffraction test (XRD) to analyze the target phase composition, obtain unit cell volume, unit cell parameters and crystal structure density and other lattice information. Its basic working principle is based on the lattice interference phenomenon between the periodic arrangement of material lattice atoms and the incident high-energy X-ray particles, so that it can receive a specific strong interference signal. Different lattice materials have different lattice interference signals, which can be used for qualitative or quantitative analysis. The test target is Cu and analyzed under Cu Kα radiation. The tube voltage of the equipment is set to 40kV, the tube current is set to 200mA, the test angle range of the sample is 5° to 120°, the scanning rate is 2° / min, and the scanning step is 0.02°.

[0062] According to some embodiments of the present invention, the ionic conductivity of the niobium-containing oxide is 1.0×10 -6 S / cm-1.0×10 -4 S / cm, for example 5.0×10 -6 S / cm, 1.0×10 -5 S / cm, 5.0×10 -5 S / cm, 1.0×10 -4 S / cm, etc. Therefore, the use of the niobium oxide containing ion conductivity in the first coating layer 21 can further improve the lithium ion transmission between the substrate 11 and the second coating layer 13, thereby improving the capacity and rate performance of the battery.

[0063] According to some further embodiments of the present invention, the ionic conductivity of the niobium-containing oxide is 1.0×10 -5 S / cm-1.0×10 -4 S / cm.

[0064] In the present invention, the test method for the ionic conductivity of niobium oxide is to use an electrochemical workstation to perform an electrochemical impedance spectroscopy (EIS) test. The assembly of the test mold battery device is to use two stainless steel electrodes to press a sample of about 100 mg under 300Mpa to assemble the mold battery. The frequency range of the electrical signal measured by EIS is 0.01Hz to 10000000Hz, and the disturbance amplitude of the AC voltage is 10mV. σ=L / RS is used to calculate the ionic conductivity, where R is the resistance value, L is the thickness, and S is the area of ​​the particle.

[0065] According to an embodiment of the present invention, the second coating layer 13 is formed on at least part of the surface of the first coating layer 12, and the second coating layer 13 includes a solid electrolyte. Thus, by forming the second coating layer 13 containing the solid electrolyte on the outer surface of the first coating layer 12, the interface contact between the positive electrode active material 10 and the solid electrolyte can be improved, the interface impedance can be reduced, and the interface stability guarantee can be provided for the electrochemical cycle of the solid-state battery.

[0066] According to some embodiments of the present invention, the oxidation potential of the solid electrolyte used in the second coating layer 13 is not higher than 4V. Since solid electrolytes with an oxidation potential not higher than 4V generally have a common problem of being incompatible with the chemical potential of conventional layered oxide positive electrode materials, such solid electrolytes with an oxidation potential not higher than 4V generally have excellent lithium ion transport properties (ionic conductivity>10 -3 S / cm), using this material as the second coating layer is beneficial to the rapid conduction of lithium ions in an all-solid-state system.

[0067] In the present invention, the test method for the oxidation potential of the solid electrolyte is a linear voltammetry (LSV) scanning test, by assembling a mold battery of conductive carbon nanotubes @ solid electrolyte / / solid electrolyte / / metallic lithium under the condition of 240Mpa, and performing a linear voltammetry (LSV) scanning test at a voltage step of 0.1mV / s to test the oxidation potential of the solid electrolyte.

[0068] According to some embodiments of the present invention, the solid electrolyte includes at least one of a sulfide solid electrolyte, an antiperovskite compound solid electrolyte, and a borohydride solid electrolyte.

[0069] As an example, the sulfide solid electrolyte includes but is not limited to Li6PS5Cl, Li 4-d Ge 1-d P d S4, Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, LiSiPSCl, LiSiPSBr and LiSiPSI, wherein 0<d<1.

[0070] As an example, the antiperovskite compound solid electrolyte includes but is not limited to Li 3-em M e m O 1-n A n Hal, wherein Hal includes at least one of F, Cl, Br and I, 1≤e≤4, 0 <m<1,0<n<1,Me Including Na + , K + , Rb + , Cs + Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , B 3+ 、Al 3+ , Ga 3+ 、In 3+ Sc 3+ , Y 3+ ,La 3+ 、Si 4+ ,Ge 4+ 、Ti 4+ 、Zr 4+ and Hf 4+ At least one of; A includes a divalent anion, for example, A includes S 2- 、Se 2- and Te 2- Specifically, when e=1, M e Including Na + , K + , Rb + and Cs + At least one of; when e = 2, M e Including Mg 2+ , Ca 2+ , Sr 2+ and Ba 2+ At least one of; when e = 3, M e Including B 3+ 、Al 3+ , Ga 3+ 、In 3+ Sc 3+ , Y 3+ and La 3+ At least one of; when e = 4, M e Including Si 4+ ,Ge 4+ 、Ti 4+ 、Zr 4+ and Hf 4+ At least one of .

[0071] As an example, the borohydride solid electrolyte includes Li r TH s , wherein 0<r, 0<s, and T includes at least one of B, C, N and Al.

[0072] According to some embodiments of the present invention, based on the total mass of the substrate 11, the content of Nb in the substrate 11 is A, and based on the total mass of the first coating layer 12, the content of Nb in the first coating layer 12 is B, and A<B. That is, the concentration of Nb in the first coating layer 12 is higher than the concentration of Nb in the substrate 11, which is beneficial to the bonding of the first coating layer 12 and the substrate 11, further improving the conduction efficiency of lithium ions, and improving the capacity and rate performance of the battery.

[0073] As an example, based on the total mass of the substrate, the Nb content A in the substrate 11 is 0.001wt%-0.6wt%, preferably 0.01wt%-0.4wt%; based on the total mass of the first coating layer, the Nb content B in the first coating layer 12 is 60.0wt%-75.0wt%, preferably 62.0.wt%-70.0wt%. Thus, by controlling the Nb content in the substrate 11 and the first coating layer 12 within the above ranges, not only can the lithium ion conduction efficiency be improved, but also the Nb in the substrate 11 can be chemically bonded with the Nb in the niobium oxide in the first coating layer 12, so that the coating structure after heat treatment is more stable, the effective solid-phase contact between the two phases is improved, and the stable solid-phase transmission of lithium ions is achieved.

[0074] According to some embodiments of the present invention, along the direction from the substrate 11 to the second coating layer 13, the volume average particle size Dv50 of the substrate 11 is C, the volume average particle size Dv50 of the niobium oxide is D, and the volume average particle size Dv50 of the solid electrolyte is E, and C≥D≥E. That is, the particles of the positive electrode active material are decreasing from the substrate 11 to the second coating layer 13, which can make the substrate 11 and the first coating layer 12 fully contact with the interface, and the first coating layer 12 and the second coating layer 13 fully contact with the interface, reduce the interface impedance, improve the transmission of lithium ions, and improve the rate performance and capacity of the battery.

[0075] As an example, along the direction from the substrate 11 to the second coating layer 13, the volume average particle size Dv50 of the substrate 11 is C, C is 3μm-20μm, preferably 3μm-10μm, and more preferably 3μm-6μm; the volume average particle size Dv50 of the niobium oxide-containing material is D, D is 0.1μm-3μm, preferably 0.1μm-1μm, and more preferably 0.1μm-0.5μm; the volume average particle size Dv50 of the solid electrolyte is E, E is 0.01μm-0.1μm, preferably 0.01μm-0.08μm, and more preferably 0.01μm-0.05μm. Therefore, by controlling the particle sizes of the substrate 11, the niobium oxide in the first coating layer 12, and the solid electrolyte in the second coating layer 13 within the above-mentioned ranges, the sufficient interface contact between the substrate 11 and the first coating layer 12 and the sufficient interface contact between the first coating layer 12 and the second coating layer 13 can be further improved, thereby improving the transmission of lithium ions and improving the rate performance and capacity of the battery.

[0076] In the present invention, Dv50 refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 50%, and is measured with reference to the standard GB / T19077-2016 using a laser particle size analyzer (eg, Malvern Master Size 3000).

[0077] According to some embodiments of the present invention, the ratio of the substrate 11 to the first coating layer 12 and the second coating layer 13 is (98.10-99.19): (0.80-1.60): (0.01-0.30). Thus, the safety performance, rate performance and capacity of the battery containing the substrate 11 can be improved.

[0078] According to the positive electrode active material of the embodiment of the present invention, it uses a niobium-doped high-nickel material as a matrix, which can effectively improve the cycle performance of the high-nickel material, and forms a first coating layer including niobium oxide on at least part of the surface of the matrix, and then forms a second coating layer including a solid electrolyte on at least part of the surface of the first coating layer, that is, the first coating layer is used as a buffer layer between the matrix and the second coating layer. On the one hand, Nb in the matrix can be chemically bonded with Nb in the niobium oxide in the first coating layer to improve the conduction of lithium ions. On the other hand, after the second coating layer including the solid electrolyte is matched with the matrix, if there is a chemical potential gradient between the two, the electrochemical window does not match, and it is easy to decompose and precipitate redox reactions of electrons and ions, which are called redox decomposition reactions of the solid electrolyte itself, and generate a space charge layer. At the same time, due to the difference in the stability of the anions of the matrix material and the solid electrolyte material, during the charge and discharge cycle, the anions of the two will diffuse to a certain extent, and the anions will be replaced at the interface. The above interface failure behaviors will lead to the occurrence of interface side reactions and increase the interface impedance. The first coating layer including niobium oxide is used as a buffer layer. On the one hand, since the chemical potential of the first coating layer including niobium oxide of the present invention is between the substrate and the solid electrolyte, it can buffer the problem of large chemical potential between the substrate and the second coating layer. On the other hand, it can inhibit the formation of lithium depletion layer at the interface between the substrate 11 and the second coating layer 13, effectively reduce the large interface resistance caused by the space charge layer, so as to protect the solid electrolyte from the high chemical potential of the positive electrode active material, and also play a role in inhibiting the interface side reaction. That is, the first coating layer including niobium oxide can reduce the space charge layer and interface side reaction between the substrate and the second coating layer, further improve lithium ion transmission, and improve the capacity and rate performance of the battery. On the other hand, after the first coating layer is introduced, the interface polarization between the substrate and the second coating layer becomes smaller, thereby improving the safety performance of the positive electrode active material. In addition, the second coating layer containing the solid electrolyte can improve the interface contact between the positive electrode active material and the solid electrolyte, reduce the interface impedance, and provide interface stability guarantee for the electrochemical cycle of the solid-state battery. Therefore, the positive electrode active material of the present invention can improve the safety performance, rate performance and capacity of the battery containing it.

[0079] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned positive electrode active material. According to an embodiment of the present invention, reference Figure 2 , the method comprising:

[0080] S100: Forming a first coating layer on at least a portion of the surface of the substrate

[0081] According to some embodiments of the present invention, the matrix includes Li 1+b (Ni 1-x1-x2 Co x1 Mnx2 ) 1-y-z Nb y M z O2, -0.5≤b≤0.3, 0.05≤x1≤0.3, 0.05≤x2≤0.3, 0<y≤0.01, 0≤z≤0.01, M includes at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B and Al, the first coating layer includes niobium oxide, the niobium oxide includes Li u Nb 1-v M′ v O3, wherein 0.5≤u≤1.2, 0≤v<1, and M′ includes at least one of Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Ti, Zr, Hf, Mn, W, Mo, B, Al, Ga, In, Ge and Sn.

[0082] Specifically, the substrate and the niobium-containing oxide are mixed and sintered at 300° C.-500° C., and kept warm for 0.5 h-12 h, for example, the sintering temperature is 300° C., 350° C., 400° C., 450° C. and 500° C., and the holding time is 0.5 h, 1 h, 3 h, 5 h, 7 h, 9 h, 11 h, 13 h, 15 h, etc., so that Nb on the surface of the substrate is bonded with Nb in the niobium-containing oxide, so that the niobium-containing oxide is physically coated on the surface of the substrate, thereby forming a first coating layer including the niobium-containing oxide on the surface of the substrate.

[0083] According to a specific embodiment of the present invention, the Li 1+b (Ni 1-x1-x2 Co x1 Mn x2 ) 1-y-z Nb y M z O2 can be a commercially available product or prepared by the following steps:

[0084] The lithium source, nickel source, cobalt source, manganese source, niobium source and M source are mixed according to the molar ratio of lithium element, nickel element, cobalt element, manganese element, niobium element and M element of 1+b:(1-x1-x2)(1-yz):x1(1-yz):x2(1-yz):y:z, and calcined at 600℃-1000℃ for 4h-20h in air or oxygen atmosphere, and then crushed and sieved to obtain a matrix.

[0085] According to some further specific embodiments of the present invention, the Li 1+b (Ni 1-x1-x2 Co x1 Mn x2 ) 1-y-z Nb yM z O2 can also be prepared by the following steps:

[0086] A nickel source, a cobalt source and a manganese source are mixed according to the molar ratio of nickel element, cobalt element and manganese element (1-x1-x2): x1:x2, and then dissolved in water to obtain a mixed salt solution of 1mol / L-3mol / L; then sodium hydroxide is dissolved into an alkaline solution with a concentration of 4mol / L-10mol / L; and ammonia water is dissolved into a complexing agent solution with a concentration of 2mol / L-10mol / L;

[0087] The mixed salt solution, alkali solution and complexing agent solution are added into the reactor for reaction. Stirring is maintained during the process. The reaction pH value and reaction temperature (pH is 10-13, reaction temperature is 50°C-70°C) are controlled. The obtained precursor slurry is subjected to solid-liquid separation, washing, drying and screening to obtain nickel-cobalt-manganese hydroxide Ni 1-x1-x2 Co x1 Mn x2 (OH)2;

[0088] Nickel cobalt manganese hydroxide is mixed with lithium source, Nb oxide and M oxide according to the molar ratio of nickel element, lithium element, niobium element and M element of (1-x1-x2)(1-yz): 1+b:y:z, calcined at 600℃-1000℃ for 4h-20h in air or oxygen atmosphere, and then crushed and sieved to obtain matrix Li 1+b (Ni 1-x1-x2 Co x1 Mn x2 ) 1-y-z Nb y M z O2.

[0089] As an example, the nickel source, cobalt source, manganese source, lithium source, niobium source and M source may be at least one of chlorides, carbonates, sulfates and oxides corresponding to the respective elements.

[0090] S200: forming a second coating layer on at least a portion of the surface of the first coating layer, wherein the second coating layer includes a solid electrolyte

[0091] The substrate forming the first coating layer and the solid electrolyte are packaged under the protection of an inert atmosphere and then mechanically mixed, and then the mixture is packaged under the protection of an inert atmosphere. Placed in a muffle furnace, mixed and sintered at 60°C-400°C, and kept warm for 0.5h-5h, for example, the sintering temperature is 60°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, etc., and the holding time is 0.5h, 1h, 3h, 5h, etc., so that the solid electrolyte is physically coated on the surface of the first coating layer, thereby forming a second coating layer including the solid electrolyte on the surface of the first coating layer.

[0092] Therefore, the above-mentioned positive electrode active material can be prepared by adopting this method, thereby improving the safety performance, rate performance and capacity of the battery containing the positive electrode active material.

[0093] It should be noted that the features and advantages described above for the positive electrode active material are also applicable to the method for preparing the positive electrode active material, and will not be described in detail here.

[0094] In a third aspect of the present invention, the present invention provides a positive electrode sheet. According to an embodiment of the present invention, the positive electrode sheet comprises the positive electrode active material described in the first aspect of the present invention or the positive electrode active material obtained by the method described in the second aspect of the present invention.

[0095] According to an embodiment of the present invention, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the positive electrode collector, the positive electrode active material layer includes the above-mentioned positive electrode active material, wherein the positive electrode collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode collector can be aluminum foil.

[0096] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0097] According to some embodiments of the present invention, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0098] According to some embodiments of the present invention, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0099] It should be noted that the features and advantages described above for the positive electrode active material and the preparation method thereof are also applicable to the positive electrode plate and will not be described in detail here.

[0100] In a fourth aspect of the present invention, the present invention provides a solid-state battery. According to an embodiment of the present invention, the solid-state battery includes the above-mentioned positive electrode sheet.

[0101] As an example, a solid-state battery includes a positive electrode sheet, a negative electrode sheet, and a solid electrolyte, wherein the solid electrolyte is located between the positive electrode sheet and the negative electrode sheet.

[0102] According to an embodiment of the present invention, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, wherein the negative electrode current collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode current collector can be a copper foil.

[0103] According to some embodiments of the present invention, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc.

[0104] In some embodiments of the present invention, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers.

[0105] In some embodiments of the present invention, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0106] In some embodiments of the present invention, the negative electrode sheet can be prepared by the following method: the above components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0107] According to some further embodiments of the present invention, the negative electrode plate may include a metal lithium plate or a lithium alloy, such as a lithium-indium alloy.

[0108] According to some other embodiments of the present invention, the solid electrolyte between the positive electrode plate and the negative electrode plate may adopt at least one of a sulfide solid electrolyte, an antiperovskite compound solid electrolyte and a borohydride solid electrolyte, and the solid electrolyte between the positive electrode plate and the negative electrode plate may be the same as or different from the solid electrolyte composition used in the second coating layer of the above-mentioned positive electrode active material, and those skilled in the art may make a selection according to actual needs.

[0109] It should be noted that the above-mentioned features and advantages described for the positive electrode plate are also applicable to the solid-state battery and will not be repeated here.

[0110] In a fifth aspect of the present invention, the present invention provides an electric device. According to an embodiment of the present invention. The electric device includes the above-mentioned solid-state battery. According to an embodiment of the present invention, the electric device may include but is not limited to a mobile phone, a laptop computer, an electric vehicle, etc.

[0111] It should be noted that the features and advantages described above for solid-state batteries are also applicable to the electrical equipment and will not be repeated here.

[0112] Below, the embodiment of the present invention is described. The embodiment described below is exemplary, is only used to explain the present invention, and cannot be interpreted as limiting the present invention. If no specific technology or conditions are indicated in the embodiment, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not indicated, they are all conventional products that can be obtained commercially.

[0113] Preparation Example 1

[0114] The oxide raw materials of lithium, niobium and zirconium were weighed according to the molar ratio of lithium element, niobium element and zirconium element of 1.005:0.995:0.005 and dispersed in an aqueous solution, and the solid content of the solution was controlled to be 40wt%. The mixture was mixed in a stirred mill for 5 hours, spray-dried, calcined at 700°C in an air atmosphere for 10 hours at a heating rate of 2°C / min, cooled in the furnace, and then crushed and sieved to obtain a composition of Li 1.005 Nb 0.995 Zr 0.005 O3-containing niobium oxide.

[0115] Preparation Example 2

[0116] The oxide raw materials of lithium, niobium and indium were dispersed in an aqueous solution according to the molar ratio of lithium element, niobium element and indium element of 1.012:0.994:0.006, and the solid content of the solution was controlled to be 40wt%. The mixture was mixed in a stirred mill for 5 hours, spray-dried, calcined at 700°C in an air atmosphere for 10 hours at a heating rate of 2°C / min, cooled in the furnace, and then crushed and sieved to obtain a composition of Li1.012 Nb 0.994 In 0.006 O3-containing niobium oxide.

[0117] Preparation Example 3

[0118] The oxide raw materials of lithium, niobium and yttrium were weighed and dispersed in an aqueous solution according to the molar ratio of lithium element, niobium element and yttrium element of 1.008:0.996:0.004, and the solid content of the solution was controlled to be 40wt%. The mixture was mixed in a stirred mill for 5 hours, spray-dried, calcined at 700°C in an air atmosphere for 10 hours at a heating rate of 2°C / min, cooled in the furnace, and then crushed and sieved to obtain a composition of Li 1.008 Nb 0.996 Y 0.004 O3-containing niobium oxide.

[0119] Preparation Example 4

[0120] The oxide raw materials of lithium, niobium and tungsten were dispersed in an aqueous solution according to a molar ratio of lithium, niobium and tungsten of 0.997:0.997:0.003, and the solid content of the solution was controlled to be 40wt%. The mixture was mixed in a stirred mill for 5 hours, spray-dried, calcined at 700°C in an air atmosphere for 10 hours at a heating rate of 2°C / min, cooled in the furnace, and then crushed and sieved to obtain a composition of Li 0.997 Nb 0.997 W 0.003 O3-containing niobium oxide.

[0121] Preparation Example 5

[0122] The lithium and niobium oxide raw materials are weighed and dispersed in an aqueous solution at a molar ratio of lithium to niobium of 1:1, the solid content of the solution is controlled to be 40wt%, and mixed in a stirred mill for 5 hours. After spray drying, sintering is carried out in an air atmosphere, calcining at 700°C for 10 hours with a heating rate of 2°C / min, cooling with the furnace, and then crushing and screening to obtain a niobium-containing oxide with a composition of LiNbO3.

[0123] The niobium-containing oxides obtained in Preparation Examples 1-5 were subjected to XRD and EIS tests, respectively, and the peak positions of the three characteristic peaks (012), (104), and (110), the unit cell volume, c / a value, the crystal structure density value, and the ionic conductivity were read and calculated. The results are shown in Table 1.

[0124] Table 1

[0125]

[0126]

[0127] As shown in Table 1, compared with the composition of LiNbO3 in Preparation Example 5, the niobium-containing oxides in Preparation Examples 1-4 are doped with other metal elements, and the peak positions (012), (104) and (110) in the XRD spectrum are shifted, and the 2θ angle corresponding to the peak position (012) in the XRD spectrum of the niobium-containing oxides in Preparation Examples 1-4 is not less than 23.7°, the 2θ angle corresponding to the peak position (104) is not less than 32.7°, and the 2θ angle corresponding to the peak position (110) is not less than 34.8°, and the unit cell volume is less than or equal to The unit cell parameters a and c satisfy c / a=2.690±0.005; the crystal structure density is 4.630±0.005g / cm 3 ; The ionic conductivity is 1.0×10 -6 S / cm-1.0×10 -4 S / cm.

[0128] Example 1

[0129] The method for preparing the positive electrode active material comprises:

[0130] Step S1: dissolving nickel sulfate, cobalt sulfate and manganese sulfate in a molar ratio of 8:1:1 among nickel element, cobalt element and manganese element to obtain a 2.5 mol / L mixed salt solution, dissolving sodium hydroxide into an alkaline solution with a concentration of 6 mol / L, dissolving ammonia water into a complexing agent solution with a concentration of 6 mol / L, and adding the mixed salt solution, the alkaline solution and the complexing agent solution into a reactor in parallel to react, keeping the stirring speed constant at 125 rpm, controlling the pH value to 11.9-12.1, and the temperature to 65°C; when the reaction is completed, keeping the temperature and the stirring speed constant, and continuing stirring for 20 minutes; then performing solid-liquid separation and washing on the obtained spherical nickel-cobalt-manganese hydroxide slurry; drying the filter cake at 120°C for 4 hours and then sieving to obtain a nickel-cobalt-manganese hydroxide material.

[0131] Step S2: Mix the nickel-cobalt-manganese hydroxide material obtained in step S1 with nano-niobium oxide powder and nano-titanium dioxide powder in a molar ratio of (Ni+Co+Mn):Nb:Ti=99:0.4:0.6. Mix the above mixture evenly with lithium hydroxide, wherein lithium hydroxide is added in a molar ratio of Li / (Ni+Co+Mn+Nb+Ti)=1.25. Sinter at 750°C for 16 hours in an oxygen atmosphere, crush and screen to obtain the positive electrode material matrix Li 1.25 (Ni 0.8 Co 0.1 Mn 0.1 ) 0.99 Nb 0.004 Ti 0.006 O2 (Dv50 is 3.0 μm). Based on the total mass of the matrix, the mass proportion of niobium in the matrix is ​​0.4 wt%.

[0132] like Figure 3 As shown, the microscopic morphology of the positive electrode material matrix prepared in Example 1 is spherical particles. After niobium is doped into the matrix, the primary particles have a needle-like rod shape with a radially arranged structure, which can relieve internal stress and prevent particle rupture.

[0133] Step S3: Prepare Li 1.005 Nb 0.995 Zr 0.005 The niobium oxide (Dv50=200nm) containing O3 and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at a mass ratio of 0.88:98.92 for dry mixing, and the mass proportion of niobium in the first coating layer is 62.5wt% based on the total mass of the first coating layer. Then, the mixture is placed in a muffle furnace for heat treatment at 400°C for 10h in an oxygen atmosphere to obtain a nickel-cobalt-manganese multi-element material with the first coating layer coating the positive electrode material matrix.

[0134] Step S4: The sulfide Li6PS5Cl (Dv50 = 40nm) and the nickel-cobalt-manganese multi-element material obtained in step S3 are placed in a ball mill mixing tank at the same time under the protection of an inert atmosphere in a mass ratio of the matrix, the first coating layer and the second coating layer of 98.92:0.88:0.2, and are packaged under the protection of an inert atmosphere and mechanically mixed for 12 hours. After mixing, the materials are placed in a vacuum furnace and heat treated at a temperature range of 100°C for 4 hours to obtain the positive electrode active material A1.

[0135] like Figure 4 As shown, the microscopic morphology of the positive electrode active material prepared in Example 1 is spherical particles, and there is an obvious island-shaped coating layer attached to the surface of the particles.

[0136] Example 2

[0137] The method for preparing the positive electrode active material comprises:

[0138] Step S1: Same as Example 1.

[0139] Step S2: Mix the nickel-cobalt-manganese hydroxide material obtained in step S1 with nano-niobium oxide powder and nano-aluminum trioxide powder in a molar ratio of (Ni+Co+Mn):Nb:Al=99:0.3:0.7. Mix the above mixture evenly with lithium hydroxide, wherein lithium hydroxide is added in a molar ratio of Li / (Ni+Co+Mn+Nb+Al)=1.15. Sinter at 750°C for 16 hours in an oxygen atmosphere, crush and screen to obtain the positive electrode material matrix Li 1.15 (Ni 0.8 Co 0.1 Mn 0.1 ) 0.99 Nb0.003 Al 0.007 O2 (Dv50 = 3.2 μm). Based on the total mass of the matrix, the mass proportion of niobium in the matrix is ​​0.3 wt%.

[0140] Step S3: The same as Example 1, except that: the composition of Li prepared in Preparation Example 2 is 1.012 Nb 0.994 In 0.006 The niobium oxide (Dv50=300nm) containing O3 and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at a mass ratio of 1.12:98.63 for dry mixing. Based on the total mass of the first coating layer, the mass proportion of niobium in the first coating layer is 62.4wt%. Finally, a nickel-cobalt-manganese multi-element material with a positive electrode material matrix coated with the first coating layer is obtained.

[0141] Step S4: The same as Example 1, except that: the sulfide Li 10 GeP2S 12 (Dv50 = 40nm) and the nickel-cobalt-manganese multi-element material obtained in step S3 are placed in a ball mill mixing tank at the same time under the protection of an inert atmosphere with a mass ratio of the matrix, the first coating layer and the second coating layer of 98.63:1.12:0.25, and are packaged and mechanically mixed under the protection of an inert atmosphere to finally obtain the positive electrode active material A2.

[0142] Example 3

[0143] The method for preparing the positive electrode active material comprises:

[0144] Step S1: Same as Example 1.

[0145] Step S2: Mix the nickel-cobalt-manganese hydroxide material obtained in step S1 with nano-niobium oxide powder and nano-boron dioxide powder in a molar ratio of (Ni+Co+Mn):Nb:B=99.3:0.2:0.5. Mix the above mixture evenly with lithium hydroxide, wherein lithium hydroxide is added in a molar ratio of Li / (Ni+Co+Mn+Nb+B)=1.20. Sinter at 800°C for 12h in an oxygen atmosphere, crush and screen to obtain the positive electrode material matrix Li 1.20 (Ni 0.8 Co 0.1 Mn 0.1 ) 0.993 Nb 0.002 B 0.005 O2 (Dv50 = 3.3 μm). Based on the total mass of the matrix, the mass proportion of niobium in the matrix is ​​0.2 wt%.

[0146] Step S3: The same as Example 1, except that: the composition of Li prepared in Preparation Example 3 is1.008 Nb 0.996 Y 0.004 The niobium oxide (Dv50=400nm) containing O3 and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at a mass ratio of 1.12:98.58 for dry mixing. Based on the total mass of the first coating layer, the mass proportion of niobium in the first coating layer is 62.6wt%. Finally, a nickel-cobalt-manganese multi-element material with a positive electrode material matrix coated with the first coating layer is obtained.

[0147] Step S4: The same as Example 1, except that the antiperovskite solid electrolyte LiOCl3 (Dv50 = 40nm) and the nickel-cobalt-manganese multi-element material obtained in step S3 are placed in a ball mill mixing tank at the same time under the protection of an inert atmosphere with a mass ratio of the matrix, the first coating layer and the second coating layer of 98.58:1.12:0.3, and then mechanically mixed after packaging under the protection of an inert atmosphere. Finally, the positive electrode active material A3 is obtained.

[0148] Example 4

[0149] The method for preparing the positive electrode active material comprises:

[0150] Step S1: Same as Example 1.

[0151] Step S2: Mix the nickel-cobalt-manganese hydroxide material obtained in step S1 with nano-niobium oxide powder and nano-tungsten trioxide powder in a molar ratio of (Ni+Co+Mn):Nb:W=99.5:0.3:0.2. Mix the above mixture evenly with lithium hydroxide, wherein lithium hydroxide is added in a molar ratio of Li / (Ni+Co+Mn+Nb+W)=1.05. Sinter at 725°C in an oxygen atmosphere for 24 hours, crush and screen to obtain the positive electrode material matrix Li 1.05 (Ni 0.8 Co 0.1 Mn 0.1 ) 0.995 Nb 0.003 W 0.002 O2 (Dv50 = 3.0 μm). Based on the total mass of the matrix, the mass proportion of niobium in the matrix is ​​0.3 wt%.

[0152] Step S3: The same as Example 1, except that: the composition of Li prepared in Preparation Example 4 is 0.997 Nb 0.997 W 0.003The niobium oxide (Dv50=300nm) containing O3 and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at a mass ratio of 1.28:98.52 for dry mixing. Based on the total mass of the first coating layer, the mass proportion of niobium in the first coating layer is 62.5wt%. Finally, a nickel-cobalt-manganese multi-element material with a positive electrode material matrix coated with the first coating layer is obtained.

[0153] Step S4: The same as Example 1, except that the borohydride LiBH4 (D50 = 40 nm) and the nickel-cobalt-manganese multi-element material obtained in step S3 are placed in a ball mill mixing tank at a mass ratio of 98.52:1.28:0.2 for the matrix, the first coating layer, and the second coating layer under the protection of an inert atmosphere, and then mechanically mixed after packaging under the protection of an inert atmosphere. Finally, the positive electrode active material A4 is obtained.

[0154] Example 5

[0155] The method for preparing the positive electrode active material comprises:

[0156] Step S1: Same as Example 1.

[0157] Step S2: Mix the nickel-cobalt-manganese hydroxide material obtained in step S1 with nano-niobium oxide powder and nano-titanium dioxide powder in a molar ratio of (Ni+Co+Mn):Nb:Ti=99:0.6:0.4. Mix the above mixture evenly with lithium hydroxide, wherein lithium hydroxide is added in a molar ratio of Li / (Ni+Co+Mn+Nb+Ti)=1.25. Sinter at 750°C for 16 hours in an oxygen atmosphere, crush and screen to obtain the positive electrode material matrix Li 1.25 (Ni 0.8 Co 0.1 Mn 0.1 ) 0.99 Nb 0.006 Ti 0.004 O2 (Dv50 = 5.2 μm). Based on the total mass of the matrix, the mass proportion of niobium in the matrix is ​​0.56 wt%.

[0158] Step S3: The same as Example 1, except that: the composition of Li prepared in Preparation Example 1 is 1.005 Nb 0.995 Zr 0.005 The niobium oxide (Dv50 = 3.0 μm) containing O3 and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at a mass ratio of 1.28:98.47 for dry mixing. Based on the total mass of the first coating layer, the mass proportion of niobium in the first coating layer is 62.5wt%. Finally, a nickel-cobalt-manganese multi-element material with a first coating layer coating the positive electrode material matrix is ​​obtained, and an X-ray diffraction test is performed on it. The XRD spectrum is as follows: Figure 5 shown.

[0159] Step S4: The same as Example 1, except that: the sulfide Li6PS5Cl (Dv50 = 40nm) and the nickel-cobalt-manganese multi-element material obtained in step S3 are placed in a ball mill mixing tank at a mass ratio of 98.47:1.28:0.25 for the matrix, the first coating layer and the second coating layer under the protection of an inert atmosphere, and then mechanically mixed after packaging under the protection of an inert atmosphere. Finally, the positive electrode active material A5 is obtained.

[0160] Example 6

[0161] The method for preparing the positive electrode active material comprises:

[0162] Step S1: Same as Example 1.

[0163] Step S2: The spherical nickel-cobalt-manganese hydroxide material obtained in step S1 is mixed with nano-niobium oxide powder and nano-titanium dioxide powder in a molar ratio of (Ni+Co+Mn):Nb:Ti=99:0.4:0.6. The above mixture is then mixed evenly with lithium hydroxide, wherein lithium hydroxide is added in a molar ratio of Li / (Ni+Co+Mn+Nb+Ti)=1.25. In an oxygen atmosphere, sinter at 750°C for 16 hours, and after crushing and screening, the positive electrode material matrix Li 1.25 (Ni 0.8 Co 0.1 Mn 0.1 ) 0.99 Nb 0.004 Ti 0.006 O2 (Dv50 = 3.0 μm). Based on the total mass of the matrix, the mass proportion of niobium in the matrix is ​​0.4 wt%.

[0164] Step S3: The same as Example 1, except that: the composition of Li prepared in Preparation Example 1 is 1.005 Nb 0.995 Zr 0.005 The niobium oxide (Dv50=250nm) containing O3 and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at a mass ratio of 0.96:98.84 for dry mixing. Based on the total mass of the first coating layer, the mass proportion of niobium in the first coating layer is 62.5wt%. Finally, a nickel-cobalt-manganese multi-element material with a positive electrode material matrix coated with the first coating layer is obtained.

[0165] Step S4: The same as Example 1, except that: the sulfide Li6PS5Cl (D50 = 50nm) and the nickel-cobalt-manganese multi-element material obtained in step S3 are placed in a ball mill mixing tank at a mass ratio of 98.84:0.96:0.2 for the matrix, the first coating layer and the second coating layer under the protection of an inert atmosphere, and then mechanically mixed after packaging under the protection of an inert atmosphere. Finally, the positive electrode active material A6 is obtained.

[0166] Example 7

[0167] The method for preparing the positive electrode active material comprises:

[0168] Step S1: dissolve nickel sulfate, cobalt sulfate and manganese sulfate according to the molar ratio of nickel, cobalt and manganese to obtain a 2 mol / L mixed salt solution, dissolve sodium hydroxide into an alkaline solution with a concentration of 8 mol / L; dissolve ammonia water into a complexing agent solution with a concentration of 6 mol / L. Add 100 L of the mixed salt solution, the alkaline solution and the complexing agent solution to the reactor in parallel for reaction, keep the stirring speed constant at 120 rpm, control the pH to 11.5-11.7, and the temperature to 60°C during the process, keep the temperature and stirring speed unchanged when the reaction is completed, continue stirring for 20 minutes, then separate the solid and liquid of the obtained nickel cobalt manganese hydroxide slurry, wash it, dry the filter cake at 105°C for 5 hours and then sieve it to obtain nickel cobalt manganese hydroxide.

[0169] Step S2: Mix the nickel-cobalt-manganese hydroxide obtained in step S1 with nano-niobium oxide powder and nano-titanium dioxide powder in a molar ratio of (Ni+Co+Mn):Nb:Ti=99:0.4:0.6. Mix the above mixture evenly with lithium carbonate, wherein lithium carbonate is added in a molar ratio of Li / (Ni+Co+Mn)=1.03. Then calcine the mixture at 850°C for 10 hours, and crush and screen the positive electrode material matrix Li 1.03 (Ni 0.6 Co 0.2 Mn 0.2 ) 0.99 Nb 0.004 Ti 0.006 O2 (Dv50 = 3.0 μm). Based on the total mass of the matrix, the mass proportion of niobium in the matrix is ​​0.4 wt%.

[0170] Step S3: The same as Example 1, except that: the composition of Li prepared in Preparation Example 1 is 1.005 Nb 0.995 Zr 0.005The niobium oxide (Dv50=250nm) containing O3 and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at a mass ratio of 0.96:98.84 for dry mixing. Based on the total mass of the first coating layer, the mass proportion of niobium in the first coating layer is 62.5wt%. Finally, a nickel-cobalt-manganese multi-element material with a positive electrode material matrix coated with the first coating layer is obtained.

[0171] Step S4: The same as Example 1, except that the borohydride LiBH4 (D50 = 50 nm) and the nickel-cobalt-manganese multi-element material obtained in step S3 are placed in a ball mill mixing tank at a mass ratio of 98.84:0.96:0.2 for the matrix, the first coating layer, and the second coating layer under the protection of an inert atmosphere, and then mechanically mixed after packaging under the protection of an inert atmosphere. Finally, the positive electrode active material A7 is obtained.

[0172] Comparative Example 1

[0173] The method for preparing the positive electrode active material comprises:

[0174] Step S1: Same as Example 1.

[0175] Step S2: Mix the nickel-cobalt-manganese hydroxide material obtained in step S1 with nano-niobium oxide powder and nano-titanium dioxide powder in a molar ratio of (Ni+Co+Mn):Nb:Ti=99:0.4:0.6. Mix the above mixture evenly with lithium hydroxide, wherein lithium hydroxide is added in a molar ratio of Li / (Ni+Co+Mn+Nb+Ti)=1.25. Sinter at 750°C for 16 hours in an oxygen atmosphere, crush and screen to obtain the positive electrode material matrix Li 1.25 (Ni 0.8 Co 0.1 Mn 0.1 ) 0.99 Nb 0.004 Ti 0.006 O2 (Dv50 = 3.0 μm), that is, D1, based on the total mass of the matrix, the mass proportion of niobium in the matrix is ​​0.4wt%. The X-ray diffraction test is performed on it, and its XRD spectrum is as follows Figure 5 As shown, compared Figure 5 From the spectra of Example 5 and Comparative Example 1, it can be seen that the XRD pattern of the positive electrode material matrix including the first coating layer in Example 5 is basically the same as the peak position of the positive electrode material matrix in Comparative Example 1, and Example 5 has an additional characteristic peak containing niobium oxide compared to Comparative Example 1 (marked with * in the figure), indicating that the first coating layer and the matrix in Example 5 still maintain phase stability after heat treatment.

[0176] Comparative Example 2

[0177] The method for preparing the positive electrode active material comprises:

[0178] Step S1: Same as Example 1.

[0179] Step S2: The spherical nickel-cobalt-manganese hydroxide material obtained in step S1 is mixed with nano-niobium oxide powder and nano-titanium dioxide powder in a molar ratio of (Ni+Co+Mn):Nb:Ti=99:0.4:0.6. The above mixture is then mixed evenly with lithium hydroxide, wherein lithium hydroxide is added in a molar ratio of Li / (Ni+Co+Mn+Nb+Ti)=1.25. In an oxygen atmosphere, sinter at 750°C for 16 hours, crush and screen to obtain the positive electrode material matrix Li 1.25 (Ni 0.8 Co 0.1 Mn 0.1 ) 0.99 Nb 0.004 Ti 0.006 O2 (Dv50 = 3.0 μm). Based on the total mass of the matrix, the mass proportion of niobium in the matrix is ​​0.4 wt%.

[0180] Step S3: The same as Example 1, except that: the composition of Li prepared in Preparation Example 1 is 1.005 Nb 0.995 Zr 0.005 The niobium oxide (Dv50=250nm) of O3 and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at a mass ratio of 0.88:99.12 for dry mixing. Based on the total mass of the first coating layer, the mass proportion of niobium in the first coating layer is 62.5wt%. Finally, the nickel-cobalt-manganese multi-element material D2 with the positive electrode material matrix coated with the first coating layer is obtained.

[0181] Comparative Example 3

[0182] The method for preparing the positive electrode active material comprises:

[0183] Step S1: Same as Example 1.

[0184] Step S2: The spherical nickel-cobalt-manganese hydroxide material obtained in step S1 is mixed with nano-niobium oxide powder and nano-titanium dioxide powder in a molar ratio of (Ni+Co+Mn):Ti=99.4:0.6. The above mixture is then mixed evenly with lithium hydroxide, wherein lithium hydroxide is added in a molar ratio of Li / (Ni+Co+Mn+Ti)=1.25. In an oxygen atmosphere, sintered at 750°C for 16 hours, crushed and sieved to obtain the positive electrode material matrix Li 1.25 (Ni 0.8 Co 0.1 Mn 0.1 ) 0.994 Ti 0.006 O2 (Dv50 = 3.0 μm).

[0185] like Figure 6 As shown, the microscopic morphology of the positive electrode material matrix without niobium modification prepared in Comparative Example 3 is spherical particles, niobium is not doped into the matrix, and the primary particles are randomly distributed multi-grain distribution.

[0186] Step S3: The same as Example 1, finally obtaining a nickel-cobalt-manganese multi-element material in which the first coating layer coats the positive electrode material matrix.

[0187] Step S4: The same as in Example 1, finally obtaining the positive electrode active material D3.

[0188] Comparative Example 4

[0189] The method for preparing the positive electrode active material comprises:

[0190] Step S1: Same as Example 1.

[0191] Step S2: Same as Example 1.

[0192] Step S3: The same as Example 1, except that niobium oxide Nb2O5 (Dv50=200nm) and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at a mass ratio of 0.79:99.01 for dry mixing, and based on the total mass of the first coating layer, the mass proportion of niobium in the first coating layer is 69.9wt%. Finally, a nickel-cobalt-manganese multi-element material with the first coating layer coating the positive electrode material matrix is ​​obtained.

[0193] Step S4: The sulfide Li6PS5Cl (Dv50 = 40nm) and the nickel-cobalt-manganese multi-element material obtained in step S3 are placed in a ball mill mixing tank at the same time under the protection of an inert atmosphere in a mass ratio of the matrix, the first coating layer and the second coating layer of 99.01:0.79:0.2, and are packaged and mechanically mixed under the protection of an inert atmosphere. After mixing, the materials are placed in a vacuum furnace and heat treated at a temperature range of 100°C for 4 hours to obtain the positive electrode active material D4.

[0194] Comparative Example 5

[0195] The method for preparing the positive electrode active material comprises:

[0196] Step S1: Same as Example 1.

[0197] Step S2: Same as Example 1.

[0198] Step S3: The sulfide Li6PS5Cl (Dv50 = 40nm) and the positive electrode material matrix obtained in step S2 are placed in a ball mill mixing tank at the same time under the protection of an inert atmosphere at a mass ratio of the matrix to the second coating layer of 0.2:99.8, and are packaged and mechanically mixed under the protection of an inert atmosphere. After mixing, the materials are placed in a vacuum furnace and heat treated at a temperature range of 100°C for 4 hours to obtain the positive electrode active material D5.

[0199] The positive electrode active materials obtained in Examples 1-7 and Comparative Examples 1-5 were assembled into solid-state batteries, and the first discharge specific capacity, first coulombic efficiency, cycle performance, rate performance and safety performance of the solid-state batteries were characterized. The characterization results are shown in Table 2, wherein the cycle curves of the solid-state batteries of Example 1 and Comparative Examples 1-5 are shown in Table 2. Figure 7 As shown:

[0200] Preparation of solid-state batteries:

[0201] The positive electrode active material, polyvinylidene fluoride binder, carbon black conductive agent and solid electrolyte sulfide Li6PS5Cl were fully dissolved in n-heptane (the mass ratio of positive electrode active material, binder, conductive agent and solid electrolyte was 70:0.5:1.5:28) to prepare a uniformly dispersed slurry, which was evenly coated on the surface of aluminum foil (loading amount was 36 mg / cm 2 ), and then transferred to a vacuum drying oven for complete drying, the obtained electrode sheet was roll-pressed, and then punched to obtain the positive electrode sheet.

[0202] Lithium-indium alloy is used as the negative electrode sheet and 100 mg of sulfide Li6PS5Cl is used as the solid electrolyte, which is pressed into sheets under a pressure of 300 MPa to obtain a solid electrolyte sheet, which is then stacked and assembled into a solid-state battery in the order of positive electrode sheet, solid electrolyte sheet and negative electrode sheet.

[0203] All the above operations were carried out in a glove box filled with argon or in a laboratory with humidity controlled at a dew point of -40 °C.

[0204] First discharge specific capacity, first cycle coulomb efficiency and cycle performance test: At 25°C, the solid-state battery was charged to 3.7V at a constant current of 0.1C to obtain the first charge specific capacity C0 of the solid-state battery, and then discharged to 2.0V at a constant current of 0.1C to obtain the first cycle discharge specific capacity C1 of the solid-state battery, and then charged and discharged at a constant current of 0.1C for 80 cycles, and the discharge specific capacity C of the 80th cycle was obtained. 80 . Battery first cycle coulombic efficiency = C1 / C0×100%. Battery capacity retention rate after 80 cycles = C 80 / C1×100%. The rate performance test is as follows: the solid-state battery is charged to 3.7V at a constant current of 0.33C, and then discharged to 2.0V at a constant current of 0.33C, to obtain the first discharge specific capacity corresponding to 0.33C; then the solid-state battery is charged to 3.7V at a constant current of 0.5C, and then discharged to 2.0V at a constant current of 0.5C, to obtain the discharge specific capacity corresponding to 0.5C; then the solid-state battery is charged to 3.7V at a constant current of 1C, and then discharged to 2.0V at a constant current of 1C, to obtain the discharge specific capacity corresponding to 1C; finally, the solid-state battery is charged to 3.7V at a constant current of 0.33C, and then discharged to 2.0V at a constant current of 0.33C, to obtain the second discharge specific capacity corresponding to 0.33C.

[0205] Safety performance test: After 80 cycles, the battery was charged at 0.1C to a fully charged state of 3.7V. The fully charged battery was disassembled, the positive electrode piece was taken out, the electrolyte and the electrode piece were transferred to a crucible, sealed, and placed in a differential scanning calorimeter (DSC) for testing (vacuum atmosphere test). The temperature at which the first peak appears in the obtained spectrum is the thermal runaway temperature.

[0206] Table 2

[0207]

[0208] In summary, it can be seen from Table 2 that the first discharge specific capacity, first cycle coulomb efficiency, 80-week cycle capacity retention rate, first discharge specific capacity corresponding to 0.33C, discharge specific capacity corresponding to 0.5C, discharge specific capacity corresponding to 1.0C, second discharge specific capacity corresponding to 0.33C and thermal runaway temperature of the solid-state batteries of Examples 1-6 are all higher than those of Comparative Examples 1-5, and the solid-state battery of Example 7 having a slightly lower nickel content than other embodiments also has higher performance, which indicates that the positive electrode active material of the present invention adopts a niobium-doped high-nickel material as a matrix, and forms a first coating layer comprising niobium oxide on at least a portion of the surface of the matrix, and then forms a second coating layer comprising a solid electrolyte on at least a portion of the surface of the first coating layer, which can improve the safety performance, rate performance and capacity of the battery containing it.

[0209] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0210] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode active material, characterized in that: include: A matrix comprising Li 1+b (Ni 1-x1-x2 Co x1 Mn x2 ) 1-y-z Nb y M z O2, -0.5≤b≤0.3, 0.05≤x1≤0.3, 0.05≤x2≤0.3, 0<y≤0.01, 0≤z≤0.01, M includes at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B and Al; The first coating layer is formed on at least a portion of the surface of the substrate, and the first coating layer includes niobium oxide, the niobium oxide includes Li u Nb 1-v M′ v O3, wherein 0.5≤u≤1.2, 0<v<1, and M′ comprises at least one of Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Ti, Zr, Hf, Mn, W, Mo, B, Al, Ga, In, Ge and Sn; The second coating layer is formed on at least a portion of the surface of the first coating layer, and the second coating layer includes a solid electrolyte; the unit cell volume of the niobium oxide is less than or equal to ; The unit cell parameters a and c satisfy c / a=2.690±0.

005.

2. The positive electrode active material according to claim 1, characterized in that The niobium oxide meets at least one of the following conditions: The peak position (012) in the XRD spectrum corresponds to Not less than 23.7°; The peak position of (104) in the XRD spectrum corresponds to Not less than 32.7°; The peak position of (110) in the XRD spectrum corresponds to Not less than 34.8°; The crystal structure density is 4.630±0.005g / cm³; The ionic conductivity of the niobium oxide is 1.0×10 -6 S / cm-1.0×10 -4 S / cm.

3. The positive electrode active material according to claim 2, characterized in that The ionic conductivity of the niobium oxide is 1.0×10 -5 S / cm-1.0×10 -4 S / cm.

4. The positive electrode active material according to claim 1 or 2, characterized in that: The oxidation potential of the solid electrolyte is not higher than 4V.

5. The positive electrode active material according to claim 4, characterized in that The solid electrolyte includes at least one of a sulfide solid electrolyte, an antiperovskite compound solid electrolyte and a borohydride solid electrolyte.

6. The positive electrode active material according to claim 5, characterized in that The sulfide solid electrolyte includes Li6PS5Cl, Li 4-d Ge 1-d P d S4, Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, LiSiPSCl, LiSiPSBr and LiSiPSI, wherein 0 <d<1。 7. The positive electrode active material according to claim 5, characterized in that The antiperovskite compound solid electrolyte includes Li 3-em M e m O 1-n A n Hal, wherein Hal includes at least one of F, Cl, Br and I, 1≤e≤4, 0 <m<1,0<n<1,M e Including Na + , K + , Rb + , Cs + Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ , B 3+ 、Al 3+ , Ga 3+ 、In 3+ Sc 3+ , Y 3+ ,La 3+ 、Si 4+ ,Ge 4+ 、Ti 4 + 、Zr 4+ and Hf 4+ At least one of; A includes a divalent anion.

8. The positive electrode active material according to claim 7, characterized in that A includes S 2- 、Se 2- and Te 2- At least one of .

9. The positive electrode active material according to claim 5, characterized in that The borohydride solid electrolyte includes Li r TH s , wherein 0<r, 0<s, and T includes at least one of B, C, N and Al.

10. The positive electrode active material according to claim 1, characterized in that Based on the total mass of the matrix, the content of Nb in the matrix is ​​A', Based on the total mass of the first coating layer, the content of Nb in the first coating layer is B, and A'<B.

11. The positive electrode active material according to claim 10, characterized in that A' is 0.001wt%-0.6wt%.

12. The positive electrode active material according to claim 11, characterized in that A' is 0.01wt%-0.4wt%.

13. The positive electrode active material according to claim 10, characterized in that B is 60.0wt%-75.0wt%.

14. The positive electrode active material according to claim 13, characterized in that B is 62.0.wt%-70.0wt%.

15. The positive electrode active material according to claim 1, characterized in that Along the direction from the substrate to the second coating layer, the volume average particle size Dv50 of the substrate is C, the volume average particle size Dv50 of the niobium oxide is D, the volume average particle size Dv50 of the solid electrolyte is E, and C≥D≥E.

16. The positive electrode active material according to claim 15, characterized in that C is 3μm-20μm.

17. The positive electrode active material according to claim 16, characterized in that C is 3μm-10μm.

18. The positive electrode active material according to claim 17, characterized in that C is 3μm-6μm.

19. The positive electrode active material according to claim 15, characterized in that D is 0.1μm-3μm.

20. The positive electrode active material according to claim 19, characterized in that D is 0.1μm-1μm.

21. The positive electrode active material according to claim 20, characterized in that D is 0.1μm-0.5μm.

22. The positive electrode active material according to claim 15, characterized in that E is 0.01μm-0.1μm.

23. The positive electrode active material according to claim 22, characterized in that E is 0.01μm-0.08μm.

24. The positive electrode active material according to claim 23, characterized in that E is 0.01μm-0.05μm.

25. The positive electrode active material according to claim 1, characterized in that The mass ratio of the substrate to the first coating layer and the second coating layer is (98.10-99.19): (0.80-1.60): (0.01-0.30).

26. A method for preparing the positive electrode active material according to claim 1, characterized in that: include: A first coating layer is formed on at least a portion of the surface of a substrate, wherein the substrate includes Li 1+b (Ni 1-x1-x2 Co x1 Mn x2 ) 1-y- z Nb y M z O2, -0.5≤b≤0.3, 0.05≤x1≤0.3, 0.05≤x2≤0.3, 0<y≤0.01, 0≤z≤0.01, M includes at least one of La, Cr, Mo, Ca, Fe, Hf, Ti, Zn, Y, Zr, Si, W, Nb, Sm, V, Mg, B and Al, the first coating layer includes niobium oxide, the niobium oxide includes Li u Nb 1-v M′ v O3, wherein 0.5≤u≤1.2, 0≤v<1, and M′ comprises at least one of Mg, Ca, Sr, Ba, Sc, Y, La, Ce, Ti, Zr, Hf, Mn, W, Mo, B, Al, Ga, In, Ge and Sn; A second coating layer is formed on at least a portion of the surface of the first coating layer, the second coating layer including a solid electrolyte.

27. The method according to claim 26, characterized in that The first coating layer is formed on at least a portion of the surface of the substrate by the following steps: The matrix and the niobium-containing oxide are mixed and sintered at 300° C.-500° C., and kept warm for 0.5 h-12 h.

28. The method according to claim 26, characterized in that The second coating layer is formed on at least a portion of the surface of the first coating layer by the following steps: The substrate forming the first coating layer is mixed with the solid electrolyte and sintered at 60° C.-400° C., and the mixture is kept at this temperature for 0.5 h-5 h.

29. A positive electrode plate, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 25 or the positive electrode active material obtained by the method according to any one of claims 26 to 28.

30. A solid-state battery, characterized in that: Including the positive electrode sheet as described in claim 29.

31. An electrical equipment, characterized in that: Including the solid-state battery as described in claim 30.

Citation Information

Patent Citations

  • Positive pole piece and application thereof

    CN117691080A

  • Positive electrode active material powder for lithium secondary batteries, electrode and solid-state lithium secondary battery

    WO2023153343A1

Cited By

  • Positive electrode active material and preparation method thereof, positive electrode plate, solid-state battery and electric equipment

    CN121439730A